Most frequent injuries in female handball players - Michaela Ragulová; Dagmar Pavlů (Karolinum Press, 2019)
Objectives. The main objective of this work was to assess the most frequent injuries in female handball players who played the premium Czech competition - MOL League Women - and the 3rd highest competition - 2nd League Women - during the 2017/2018 season. The objectives also included ascertaining whether preventive and compensation exercises are included in the teams' training units. Methods. The questionnaire method was selected. A non-standard questionnaire was sent out to all players in the two competitions. A total of 112 questionnaires were analysed. Results. Injuries in the ankle area were found to the most frequent type of injury, reported by 56.3% respondents. Injuries in the hand and knee areas followed, concerning 50.9% and 46.4% respondents, respectively. Recovery and compensation procedures were found to be inadequately used in the handball players' regime.